Sosialisasi dan Pelatihan Pembuatan Kerajinan Limbah Kulit Jagung di Desa Randualas Sendang Seloaji - Dian Novia Ningtias; Karisma Laili Khasanah; Evi Priyana; Annisa Khofiyatus Sholikhah; Ferninda Dea Agdiani; Arum Suproborini (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Randualas Village is located in Kare District, Madiun Regency and has abundant potential for corn plant biological resources. The available corn husk waste sometimes only becomes a pile of garbage and has not been utilized optimally. Community service aims to foster insight in the Randualas village community and the economic value of corn husk waste. The method of implementing community service is through socialization and training in making handicrafts from corn waste. The results of this activity are the creation of increased community insight in the management of corn husk waste and the results of handicrafts that have sales value from corn waste. Based on the results of the pre-test and post-test, an increase in insight of 50% was obtained. The handicrafts produced are not only used to beautify the interior of residents' homes but are also sold to increase residents' income. This activity can increase insight, creativity, and income of village residents. The follow-up to this activity will be carried out continuous training and efforts are made so that the handicrafts can be marketed online so that they can improve the economy of Randualas village residents.